Nurse preparedness in emergency department during the Covid-19 outbreak; nurse’s perspective - Khairina, Ilfa; Nelwati, Nelwati; Maisa, Esthika Ariany; Rahman, Dally (University of Muhammadiyah Malang, 2023)
Introduction: The Emergency Department (ED) is one of the first accesses reached by people affected by Covid-19 or suspected of having Covid-19. Changes in health services in the ED during the Covid-19 Outbreak and the adaptation of the new normal made ED health services and adjustments by nurses. The ED is one area that has the potential to have a high risk of transmitting Covid-19. Objectives: This study aimed to determine the experience of emergency room nurses in dealing with the Covid-19 outbreak at a government hospital in Padang. Methods: This study is qualitative with semi-structured interviews conducted with nurses who serve in the ED, who were selected based on inclusion criteria. These nurses had served in the ER during the Covid-19 outbreak for a minimum of 6 months. The results of the interviews were processed using the Collaizi technique. The participants in this study were 5 emergency room nurses. Results: The results obtained 3 themes and 11 sub-themes. The themes that can be found are Nurses' Preparation for the Pandemic, Coordination and Health Promotion with Families, and Hospital and Emergency Room Readiness. Conclusions: Hospital management have to prepare and coordinate human resources and facilities following non-natural disaster conditions so that the nurse's response ability in dealing with the Covid-19 pandemic becomes responsive and better.